Pontemazines A and B, phenazine derivatives containing a methylamine linkage from Streptomyces sp. UT1123 and their protective effect to HT-22 neuronal cells. Issue 22 (15th November 2015) - Cha, Jin Wook; Lee, Seung Il; Kim, Min Cheol; Thida, Mya; Lee, Jae Wook; Park, Jin-Soo; Kwon, Hak Cheol
Graphical abstract: Abstract: New phenazine derivatives with a methylamine linker, Pontemazines A (1 ) and B (2 ), were isolated from the culture broth of Streptomyces sp. UT1123. The structures of compounds1 and2 were determined by NMR spectroscopy and high-resolution mass spectrometry. These compounds consist of a 9-mehoxyphenazine connected to a benzamide functional group by a unique methylamine linker instead of the more common methyl ether. Pontemazines A and B possess a neuronal cell protective effect on glutamate-induced mouse hippocampal HT-22 cell damage.